Deficit Budget as a Hidden Tax: An Application in Bangladesh - Akon , Riaz; Saha , Mallika (Economic Journal of Development Issues, 2024)
Since the 1970s, Bangladesh has faced persistent budget deficits, and this paper aims to examine their influence on the economy, exploring how deficit financing, such as borrowing from banks, can lead to inflationary pressures, while also uncovering the hidden costs of budget deficits and offering recommendations to promote economic growth and stability, ultimately aiding policymakers in making informed decisions to address these challenges. This paper uses the secondary data to analyze the data and data was collected from 2000 from 2023. Bangladesh has experienced budget deficits, implemented expansionary monetary policies, and maintained relatively stable inflation, with the government aiming to tackle these challenges by improving fiscal management, enhancing the tax structure, and reducing reliance on borrowing. The study shows that expansionary monetary policies in the country have contributed to significant growth in the money supply (M2) over the past few decades. Despite these pressures, inflation in Bangladesh has remained relatively stable, averaging around 5.5% from 2000 to 2023.